Reasons for not reporting patient safety incidents in general practice: A qualitative study - Kousgaard, Marius Brostrøm (Informa Healthcare, 2012)
OBJECTIVE: To explore the reasons for not reporting patient safety incidents in general practice. DESIGN: Qualitative interviews with general practitioners and members of the project group. SETTING: General practice clinics in the Region of Northern Jutland in Denmark. SUBJECTS: Twelve general practitioners. MAIN OUTCOME MEASURES: The experiences and reflections of the involved professionals with regard to system use and non-use. RESULTS: While most respondents were initially positive towards the idea of reporting and learning from patient safety incidents, they actually reported very few incidents. The major reasons for the low reporting rates are found to be a perceived lack of practical usefulness, issues of time and effort in a busy clinic with competing priorities, and considerations of appropriateness in relation to other professionals. CONCLUSION: The results suggest that the visions of formal, comprehensive, and systematic reporting of (and learning from) patient safety incidents will be quite difficult to realize in general practice. Future studies should investigate how various ways of organizing incident reporting at the regional level influence local activities of reporting and learning in general practice.